Studi Pemasaran Jasa Pendidikan: Faktor-Faktor yang Memengaruhi Mahasiswa Memilih Program Studi Baru - Ismaulina Ismaulina; Ali Muhayatsyah; Suryani Suryani; Putri Sri Anita (Jurnal Ilmu Manajemen, 2021)
Instititut Agama Islam Negeri (IAIN) Lhokseumawe is the only Islamic education campus in Lhokseumawe city, which one of its faculties is the Faculty of Islamic Economics and Business, consisting of Sharia banking and Sharia Accounting study programs. This research tries to determine factors influencing the students' decision to choose the new study program in the Faculty of Islamic Economics and Business, IAIN Lhokseumawe. This research used analysis factor methods using SPSS. The study samples are Sharia banking and Sharia Accounting students. The research results explained that the investigated two-factor groups: the first-factor group includes the place, process, physical evidence, price, product, decision, and economy. The second-factor group includes positive issues and promotion. The positive issue factor is the highest and dominated the students' decision to choose the study programs. The following factors included place, process, physical evidence, price, product, promotion, decision, and economy. Thus, there is no difference between factor 1 and factor 2 variables influencing the students' decision when choosing the departments. This research is limited to two study programs in an Islamic higher education institution. Future research can involve students' parents and compare with other study programs using other research methods to get a complete picture to deepen the factors influencing students to choose a new study program.